Determinants of Women’s Well-Being : The Mediating Role of Work-Family Conflict and the Moderating Role of Organizational Support - Naning Kristiyana; Siti Chamidah; Premi Wahyu Widyaningrum; Astutik Dwi Rahayu (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Women’s increasing participation in the workforce is often accompanied by work-family conflict due to the demands of dual roles. The extent of this conflict is influenced by individual and contextual factors, including gender role ideology, spouse support, and work flexibility. Organizational support also plays an important role in mitigating these challenges and enhancing women’s well-being.Purpose: This study examines the determinants of women’s well-being by analyzing the effects of gender role ideology, spouse support, and work schedule flexibility, with work-family conflict as a mediator and perceived organizational support as a moderator. Design/methodology/approach: A quantitative approach was employed using data from 210 married female workers in East Java, Indonesia. The analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM). Findings/Results: The findings reveal that gender role ideology, spouse support, and work schedule flexibility significantly affect work–family conflict and indirectly influence well-being through its mediating role. Additionally, perceived organizational support moderates the relationship between work-family conflict and well-being. Conclusion: Egalitarian gender role ideology, strong spouse support, and flexible work arrangements reduce work-family conflict, which in turn enhances women’s well-being. Organizational support further weakens the negative impact of work-family conflict, emphasizing the importance of supportive workplace environments. Originality/value (State of the art): This study develops a comprehensive moderated mediation model to explain women’s well-being. It highlights the role of organizational support in buffering the adverse effects of work-family conflict, contributing to the broader discourse on gender equality and workplace inclusion. Keywords: gender role ideology, spouse support, work schedule flexibility, work-family conflict, perceived organizational support, well-being